Benefit From Intentional Listening Skills In Activating Teaching: Intentional Listening Of The Prophet As A Model - Malallah Hussein, Husam (Opción, 2019)
The present research is to focus on the skill of listening and its role in acti- vating communication between the speaker and the listener and strengthen their impact between them, the research dealt with the literature of modern education on the subject of communication in general and listening in particu- lar and written by leading international authors famous in this area, as well as what our ancestors of Muslim scientists wrote about the year The Prophet -in his communication with all people believer and unbelievers of their world and ignorance, and how he absorbed - session all of his skill and high-end eth- ics, and the fruit of the blessing of his wise call - and blessing those skills the best generation known to mankind to represent the ethics and behavior of the Prophet in his companions God bless them all Doanh. The researcher has col- lected some attitudes from the year of the Prophet - and extracted what relat- ed to effective communication through the skill of listening in particular and its positive impact on the recipient. The present research has drawn the de- sired benefits of this skill for adoption and application in teaching, education, education and advocacy, and recommended all those concerned with teaching and teaching to apply the skill of listening in all educational institutions to activate their teaching capacity and increase their educational efficiency to improve the level of learners from their low reality.